Role of Notary in Capital Market: Making GMS Minutes Online During Covid-19 - Rais Firdaus Handoko; Budi Santosa (Jurnal Akta, 2020)
In early 2020, the world was shocked by the rapid spread of the novel coronavirus disease known as the corona virus disease which came out at the end of 2019 (COVID-19), so that the whole world took many policies with online system, including lectures and notary activities. The purpose of this paper is to explain controversy over the principle of lex specialis derogate legi generalis in the capital market notary and legality of making the deed of the minutes of the GMS online by a capital market notary can provide justice for notaries. This research used a normative juridical research with the specification of the research was carried out descriptively and analytically. Normative research uses secondary data types. The data collection method used by conducting Library Research and the techniques used in describing and processing the collected data are qualitative descriptions. This writing can be concluded that the deed of the minutes of the GMS of capital market companies in accordance with Article 5 paragraph (1) of the Electronic Information and Transaction Law includes the so-called electronic documents which are valid evidence, while in Article 16 letter m of the Law on Notary Position, it is stated in the explanation of this Article. "That the notary must be physically present and sign the deed before the audience and witnesses". The author's suggestion is to revise the Law on the Position of Notary Public, legalize the formation of GMS minutes online both during the corona virus pandemic and after the end of the virus, so that these rules can adapt to the needs of today's life which are completely electronic, internet, digitization, and computerized.